Immunohistochemical and Molecular Characterization of the Human Periosteum - Sönke Percy Frey; Hendrik Jansen; Stefanie Doht; Luis Filgueira; Rene Zellweger (The Scientific World Journal)
Purpose. The aim of the present study was to characterize the cell of the human periosteum using immunohistological and molecular methods. Methods. Phenotypic properties and the distribution of the cells within the different layers were investigated with immunohistochemical staining techniques and RT-PCR, focussing on markers for stromal stem cells, osteoblasts, osteoclasts and immune cells. Results. Immunohistochemical results revealed that all stained cells were located in the cambium layer and that most cells were positive for vimentin. The majority of cells consisted of stromal stem cells and osteoblastic precursor cells. The density increased towards the deeper layers of the cambium. In addition, cells positive for markers of the osteoblast, chondrocyte, and osteoclast lineages were found. Interestingly, there were MHC class II-expressing immune cells suggesting the presence of dendritic cells. Using lineage-specific primer pairs RT-PCR confirmed the immunofluorescence microscopy results, supporting that human periosteum serves as a reservoir of stromal stem cells, as well as cells of the osteoblastic, and the chondroblastic lineage, osteoclasts, and dendritic cells. Conclusion. Our work elucidates the role of periosteum as a source of cells with a high regenerative capacity. Undifferentiated stromal stem cells as well as osteoblastic precursor cells are dominating in the cambium layer. A new outlook is given towards an immune response coming from the periosteum as MHC II positive immune cells were detected.